Association of autoimmunity and atopy with vitiligo: A case control study. - Chapagain,Pukar (2019)
SUMMARY: Background: Vitiligo is an acquired idiopathic condition of localized depigmentation that result from progressive loss of functional melanocytes. The exact aetiology of vitiligo is poorly understood but autoimmune theory is most accepted. Objective: The objective of this study was to study the association of autoimmunity and atopy with vitiligo and compare with the healthy control group. Methods: In a prospective case-control study, we analyzed 439 cases of vitiligo for personal history of autoimmune disease, personal and family history of atopy, thyroid function test (TFT), Antinuclear Antibodies (ANA) and Anti-TPO antibodies and compared with 109 healthy volunteers. Results: Personal history of atopy (aOR 3.507 95% CI 1.728-7.116), family history of vitiligo (aOR 8.333 95% CI 2.502-27.756), eosinophilia (aOR 2.577 95% CI 1.075-6.179), increased thyroid stimulating hormone (aOR 8.406 95% CI 1.095-64.536) and anti-thyroid peroxidase antibody (aOR 2.359 95% CI 1.197-4.649) was independently associated with vitiligo. Conclusion: Vitiligo is strongly associated with autoimmunity and personal history of atopy and thyroid disorders and tests to detect TFT and Anti-TPO are useful markers in vitiligo while test todetect ANA has limited relevance.